A Systematic Review of Teachers’ Causal Attributions: Prevalence, Correlates, and Consequences - Wang, Hui; Hall, Nathan C. (Frontiers in Psychology, 2018)
The current review provides an overview of published research on teachers’ causal attributions since 1970s in the context of theoretical assumptions outlined in Weiner’s attribution theory (1972, 1985, 2000, 2001, 2010). Results across 79 studies are first examined with respect to the prevalence of teachers’ interpersonal causal attributions for student performance and misbehavior, as well as intrapersonal attributions for occupational stress. Second, findings showing significant relations between teachers’ attributions and their emotions and cognitions, as well as student outcomes, are discussed. Third, an overview of results showing the prevalence and implications of teachers’ causal attributions to be moderated by critical background variables is also provided. Finally, observed themes across study findings are highlighted with respect to the fundamental attribution error and the utility of Weiner’s attribution theory for understanding how teachers’ explanations for classroom stressors impact their instruction, well-being, and student development.